Estimation Of Percent Body Fat Content By Anthropometry In Young Males And Females - PANDURANG M. NARHARE; INDLA DEVASENA (International Journal of Pharma and Bio Sciences, 2011)
The mortality and morbidity due to obesity has increased in recent decades. So present study was done to find out percent body fat content for early detection of obesity in young age group by measuring skin fold and girth and results obtained were compared.Body density was calculated using mean of four skin fold measurements by using the equations of Durnin and Womersley. Percent body fat content was calculated from the body density by Siri’s equation and prediction equations and constants presented by McArdle et al. The mean percent body fat content by skin fold method in young males was 15.87±3.85 and 14.90±3.81 by girth method. In young females the mean percent body fat content by skin fold method was 25.03±4.54 and 23.74±4.59 by girth method. 10% of young males and 16.67% young females were found to be obese. The correlation coefficient between skin fold and girth methods in young males and females was 0.98.So we conclude that girth method can also be used to estimate percent body fat content, because of its simplicity & inexpensive instruments for measurements.